Growth performance, hematological parameters and lipid profile of mice treated with black seed oil and vitamin-E - Mustari, Afrina; Sujan, Khaled Mahmud; Moni, Debasree Sarker; Alam, Mahabub; Miah, Mohammad Alam; Islam, Md Kamrul (Asian Journal of Medical and Biological Research, 2021)
Nigella sativa (Black seed) has been recognized as one of the most popular herbs in many parts of the world for centuries and used as folk medicine to cure different kinds of diseases. Vitamin E is well known for its antioxidative and anti-inflammatory properties, and has been studied in the prevention of cardiovascular disease (CVD). The present study was performed to determine the effect of black seed oil and Vit-E on growth performance and blood biochemistry in mice. A total of 40 mice weight between 25-27 gm were used for conducting the research. At first, the mice were randomly divided into 4 groups consisting 10 mice in each group. Group A served as the control group whereas Group B was administered black seed oil @ 0.5 ml/kg/day, Groups C was taken vitamin E @ 200 mg/kg/day and Group D was received both black seed oil @ 0.5 ml/kg/day + vitamin E @ 200 mg/kg/day respectively for 42 days. Result showed that, body weight of B, C and D group revealed a significant decrease than the control group (p<0.05). Hemoglobin concentration (Hb) and Total Erythrocyte Count (TEC) showed a significant change in B, C and D group than the control group (p<0.05). On the other hand, Total Leukocyte Count (TLC) and Packed Cell Volume (PCV) were insignificant. The results of biochemical test explored that serum cholesterol and triglyceride value decreased significantly whereas HDL increased significantly in black seed oil, Vit-E treated groups than the control group (p<0.05). But the LDL showed no change after treatment. It could be concluded that the black seed oil and Vit-E can be used in the therapeutic strategy of obesity, anemia and coronary diseases. Asian J. Med. Biol. Res. 2021, 7 (2), 132-137